The Influence of Organizational Citizenship Behavior and Quality of Work Life on Employee Performance - Utomo, Sudibyo Budi (Indonesian Journal of Islamic Economics and Finance, 2023)
Organizations generally believe that excellence must be maintained in order to increase performance, because performance basically affects employee performance as a whole. Therefore, to pursue and improve performance, Organizational Citizenship Behavior and Quality of Work Life are needed. This research examines how much influence Organizational Citizenship Behavior and Quality of Work Life have on employee performance. This research aims to find out and obtain data related to the influence of organizational citizenship behavior and quality of work life on employee performance, where this data will be used as material in preparing a thesis. The method used in this research is descriptive and verification methods. The research population consisted of 56 employees, and the sampling technique used in this research was non-probability sampling. Data collection techniques use interviews, observation, questionnaires and documentation. Data analysis in this study used multiple linear regression analysis. Through the results of data processing, a prediction model for the variables organizational citizenship behavior and quality of work life on employee performance can be formed as follows = 7.482 + 0.197X1 + 0.410X2. The results of data processing show that the R2 value is 0.547 or 54.7%, this illustrates that the contribution of organizational citizenship behavior and quality of work life to the increase or decrease in employee performance is 45.3% and the remaining 0.453 or 45.3% is the contribution of other variables not included in the model proposed in the research. Organizational citizenship behavior and quality of work life together have a positive and significant effect on organizational citizenship behavior on employee performance at Surya Toserba Kadipaten, Majalengka Regency.